Does brand love matter to casual restaurants? A multi-group path analysis. Issue 5 (4th July 2021) - Shen, Ye; Huang, Shuyue; Choi, Hwan-Suk Chris; Morrison, Alastair M.
ABSTRACT: Previous research indicates that just satisfying customers is insufficient for retaining loyalty. Therefore, this research explores how to inspire and retain loyalty by adding an important construct, brand love, to the value-satisfaction-loyalty chain. Data were collected from guests of casual dining restaurants. The measurement scales adopted in this research were derived from the previous literature and adapted to the restaurant context. A multi-group path analysis was conducted to investigate whether the effects of brand love varied with gender, age, and income groups. This research confirmed that brand love is the outcome of excellent perceived value and a high level of satisfaction, and brand love is more important than perceived value and satisfaction in inspiring revisit intentions. This investigation emphasizes the importance of brand love for certain segments: women, Generation Xers, and people with higher incomes. It fills a gap in the literature by including brand love in the value-satisfaction-loyalty framework.